Ethono Medicinal Study of Parachinar, Kurram Valley (FATA) KPK, Pakistan - Wahid Hussain, Javid Hussain, Sajid Hussain, Zabta khan Shinwari, Roshan Ali, Abdul Basir (Journal of Applied Pharmaceutical Science, 2013)
The Present studies were carried out to identify the medicinal plants, folk knowledge of medicinal plants and to motivate the inhabitants of Kurram Agency to use their knowledge in a better way. The area has high potential regarding its biodiversity as well as valuable medicinal plants. The Information was collected from traditional experts regarding 26 medicinally important species belonging to 17 families. Asparagus officinalis Royal is used for constipation, Berberis lyceum Royal is used for urine and chest problems, Cichorium intybus Linn is used as antipyretic, Foeniculum vulgare Millis is used for stomach problems, blood purifier & intestinal diseases, Fumaria indica Haussk is used as a drug for blood purification and as antipyretic, Quercus ilex Rox is used in diabetes, Seriphidium kurramensis L is being used as a good anti-malarial drug and a vermifuge and Ziziphora teniour Linn is used as carminative and for colic pain. These specimens were deposited in the herbarium at plant sciences department, Kohat University of Science and Technology, Pakistan for further medicinal investigation.
Keywords: Ethno medicinal, chemical constituent, Medicinal plants, Mercuric Chloride, Ethyl alcohol, Kurram Agency Pakistan.